2021
DOI: 10.1210/jendso/bvab175
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mineralocorticoid Receptor Antagonism on Changes in NT-proBNP Among Persons With HIV

Abstract: Subclinical myocardial dysfunction is prevalent among well-treated persons with HIV (PWH). We have previously demonstrated unique renin-angiotensin-aldosterone system physiology among PWH with metabolic dysregulation. Mineralocorticoid receptor blockade may be a targeted treatment strategy for subclinical heart disease in PWH. Forty-six PWH were randomized to receive either eplerenone 50 mg daily or placebo in a 6-month randomized, double-blinded, placebo-controlled trial. We assessed changes in N-terminal pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…''The exact mechanism remains unclear, but preclinical data suggest that excess aldosterone may drive inflammatory cytokine production, vascular inflammation and fibrosis, oxidative stress, and endothelial dysfunction.'' Srinivasa and colleagues at Massachusetts General Hospital designed a double-blind, placebo-controlled study to evaluate the effects of eplerenone, a selective aldosterone receptor antagonist, on the progression of inflammation and cardiovascular disease in PWH [5]. The initial data, collected from 26 adequately treated PWH without known ASCVD, showed that treatment with eplerenone for 12 months significantly reduced arterial inflammation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…''The exact mechanism remains unclear, but preclinical data suggest that excess aldosterone may drive inflammatory cytokine production, vascular inflammation and fibrosis, oxidative stress, and endothelial dysfunction.'' Srinivasa and colleagues at Massachusetts General Hospital designed a double-blind, placebo-controlled study to evaluate the effects of eplerenone, a selective aldosterone receptor antagonist, on the progression of inflammation and cardiovascular disease in PWH [5]. The initial data, collected from 26 adequately treated PWH without known ASCVD, showed that treatment with eplerenone for 12 months significantly reduced arterial inflammation.…”
mentioning
confidence: 99%
“…Srinivasa and colleagues at Massachusetts General Hospital designed a double-blind, placebo-controlled study to evaluate the effects of eplerenone, a selective aldosterone receptor antagonist, on the progression of inflammation and cardiovascular disease in PWH [5]. The initial data, collected from 26 adequately treated PWH without known ASCVD, showed that treatment with eplerenone for 12 months significantly reduced arterial inflammation.…”
mentioning
confidence: 99%